Meningkatkan Pemahaman Sadar Bencana Melalui Sosialisasi Mitigasi Bencana Kebakaran Di SDN Bluru Kidul 2 - Risti Dinar Larasati; Putri Pratami Susanti; Dzaki Syahriar Ahmad; Diyanti Almira Brylyani; Binti Azizatun Nafi’ah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Fire is one of the disasters that can damage the environment, and has a significant impact on the community, including children who are vulnerable groups. Therefore, disaster mitigation education, especially for children, is very important to reduce the risk and impact of the losses caused. In this service, the socialization of fire disaster mitigation activities was carried out on August 16, 2024 at SD Negeri Bluru Kidul 2 Sidoarjo. The activity, organized by students of the National Development University “Veteran” of East Java in collaboration with the Sidoarjo Regency Fire Department, included the delivery of material on the causes and handling of fires, demonstrations of the use of fire extinguishers, and interactive activities designed to increase student understanding and involvement. The results of the activities showed a significant increase in children's awareness and knowledge of fire mitigation. These findings highlight the importance of implementing disaster mitigation education programs as an effective preventive measure to minimize the impact of fires in the future.